Food price changes and farm households' welfare in Nigeria: Direct and indirect approach - C. P. Adekunle; Sakiru Oladele Akinbode; Adebayo Musediku Shittu; S. Momoh (Journal of Applied Economics, 2020)
This paper analyzed the welfare effects of price changes over categories of farm households in Nigeria taking into consideration the dual role of farm households as both consumer and producer of food between 2010-2016. This study attempts to shed some light on the differences between the direct approach and indirect. Estimated Compensating Variation reveals that 79.0% of farm households were net food buyers and suffered welfare loss (mean = 2.98) with the mean expenditure of N529, 397.5 per annum while 21.0% were net food sellers and enjoyed welfare gain (mean = - 1.66) with the mean expenditure of N513, 755.7 per annum. Cereal was identified as food for which the households were most vulnerable to price shocks. When adjustments are allowed, households can adapt their consumption and production patterns resulting in lower deteriorations in welfare with significant differences across quintiles. Therefore, efforts to mitigate extreme price spikes are relevant for improved overall household welfare.
Keywords: 330; demand elasticities; Food prices; Nigeria; supply elasticities; welfare